A web-based application for eliciting narrative discourse from Greek-speaking people with and without language impairments - Stamouli, Spyridoula; Nerantzini, Michaela; Papakyritsis, Ioannis; Katsamanis, Athanasios; Chatzoudis, Gerasimos; Dimou, Athanasia-Lida; Plitsis, Manos; Katsouros, Vassilis; Varlokosta, Spyridoula; Terzi, Arhonto (Frontiers in Communication, 2023)
In this paper we present a web-based data collection method designed to elicit narrative discourse from adults with and without language impairments, both in an in-person set up and remotely. We describe the design, methodological considerations and technical requirements regarding the application development, the elicitation tasks, materials, and guidelines, as well as the implementation of the assessment procedure. To investigate the efficacy of remote elicitation of narrative discourse with the use of the technology-enhanced method presented here, a pilot study was conducted, aiming to compare narratives elicited remotely to narratives collected in an in-person elicitation mode from ten unimpaired adults, using a within-participants research design. In the remote elicitation setting, each participant performed the tasks of a narrative elicitation protocol via the web application in their own environment, with the assistance of an investigator in the context of a virtual meeting (video conferencing). In the in-person elicitation setting, the participant was in the same environment with the investigator, who administered the tasks using the web application. Data were manually transcribed, and transcripts were processed with Natural Language Processing (NLP) tools. Linguistic features representing key measures of spoken narrative discourse were automatically calculated: linguistic productivity, content richness, fluency, syntactic complexity at clausal and inter-clausal level, lexical diversity, and verbal output. The results show that spoken narratives produced by the same individuals in the two different experimental settings do not present significant differences regarding the linguistic variables analyzed, in sixty six out of seventy statistical tests. These results indicate that the presented web-based application is a feasible method for the remote collection of spoken narrative discourse from adults without language impairments in the context of online assessment.